2018
DOI: 10.1002/jcp.27369
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase kinase 1 contributes to cisplatin resistance of ovarian cancer through EGFR activation

Abstract: Patients with ovarian cancer frequently develop acquired drug resistance after the long-term chemotherapy, leading to disease progression. Enhanced epithelial-mesenchymal transition (EMT) has been implicated in chemoresistance of ovarian cancer cells; however, the molecular mechanisms involved are largely undefined. Pyruvate dehydrogenase kinase 1 (PDK1), a key regulatory enzyme in glucose metabolism, has been recognized as a gatekeeper of the Warburg effect, a hallmark of cancer. In this study, the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…In the PDHA1-knockout cells, cell viability was partially rescued by about 40% compared with IQ-treated wild type A549 cells. The results might due to off-targets of IQ or another target of PDK1, including EGFR, HGF-MET, and PARL [22][23][24]. Thus, we suggest that IQ significantly induced mitochondrial ROS production by inhibiting PDK1 activity and thereby induced apoptotic cell death in the A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…In the PDHA1-knockout cells, cell viability was partially rescued by about 40% compared with IQ-treated wild type A549 cells. The results might due to off-targets of IQ or another target of PDK1, including EGFR, HGF-MET, and PARL [22][23][24]. Thus, we suggest that IQ significantly induced mitochondrial ROS production by inhibiting PDK1 activity and thereby induced apoptotic cell death in the A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…PDK1, a key enzyme regulates glucose metabolism, attenuates ROS production and prevents hypoxia-induced apoptosis 34 . Zhang et al 35 has reported that PDK1 stimulates EMT program, resistance to cisplatin and increases ovarian cancer growth. In addition, it has been recognized as a gatekeeper of the Warburg effect 35 through inhibition of PDH enzyme, , c, d, e, f) show the UCP2, PDK1, PDH, AMPK and MCT1 expression in T24 cell line after E. coli infection at different MOI and durations, compared to uninfected T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 35 has reported that PDK1 stimulates EMT program, resistance to cisplatin and increases ovarian cancer growth. In addition, it has been recognized as a gatekeeper of the Warburg effect 35 through inhibition of PDH enzyme, , c, d, e, f) show the UCP2, PDK1, PDH, AMPK and MCT1 expression in T24 cell line after E. coli infection at different MOI and durations, compared to uninfected T24 cells. #, ## express the significant difference (p ≤ 0.01) and (p ≤ 0.001) of gene expression with respect to the infection duration and MOI respectively, obtained by one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…Dicumarol, a coumarin compound, has been found to inhibit PDK1 and suppress ovarian cancer tumor growth in vivo 22 . A recent study demonstrated PDK1 contributes to cisplatin resistance of ovarian cancer through EGFR activation and promotes epithelial-mesenchymal transition 23 . In this study, we focused on the clinical significance, functional roles, and downstream mechanisms of PDK1 in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%